النظام القانوني للجمعيات في الجزائر - بلال بن لطيف; أمير بقور (My University, 2024)
Summary : This study, entitled “The Legal System of Associations in Algeria,” focuses on associations through the rules which organized for the establishment of institutions, and their role in awareness and sensitization, by exploring the needs and shortcomings that concern the citizen in order to take them into consideration by the competent authorities, because they are as the second eye of the public authorities in the country. From the above, we see the importance of associations in the life of the citizen and the state, as they are an essential partner, especially after the constitutional amendment of 2020. Accordingly, this study was divided into two chapters: the first chapter, entitled The legal system for establishing associations, and the second chapter, entitled The organization and functioning of associations. Since the right to establish associations is guaranteed constitutionally and is a social demand, most successive constitutions have enshrined this right, the most recent among them is the Constitutional Amendment of 2020, which stipulates, through Article 53, that the right to establish associations is guaranteed, and can be be practiced as soon as it is declared, and it regulated in an organic law. ............................... الملخص: تتناول هذه الدراسة المعنونة بـ:"النظام القانوني للجمعيات في الجزائر" تسليط الضوء على الجمعيات من خلال القواعد المنظمة لنشأتها ودورها في التوعية والتحسيس، من خلال إستطلاع الحاجيات والنقائص التي تهم المواطن من اجل أخذها بعين الاعتبار من قبل السلطات المختصة، فهي بمثابة العين الثانية للسلطات العامة في الدولة. وعلى ضوء ما سبق تظهر أهمية الجمعيات في حياة المواطن والدولة على السواء، فهي شريك أساسي خاصة بعد التعديل الدستوري لسنة 2020، وعليه فقد تم تقسيم هذ الدراسة إلى فصلين: الفصل الأول بعنوان النظام القانوني لتأسيس الجمعيات، والفصل الثاني بعنوان تنظيم الجمعيات وسيرها. وكما أن حق إنشاء الجمعيات مكفول دستوريا ومطلب اجتماعي، فجل الدساتير المتعاقبة رسخت فيها هذا الحق فيها، وأخرها التعديل الدستوري الأخير لسنة 2020، الذي جاء فيه من خلال مادته 53 على ان حق انشاء الجمعيات مضمون ويمارس بمجرد التصريح به وينظم في قانون عضوي. ...................... Résumé : Cette étude, intitulée "Le système juridique des associations en Algérie", se concentre sur les associations à travers les règles qui les organisent pour la création d'institutions, ainsi que leur rôle dans la sensibilisation et la mobilisation, en explorant les besoins et les lacunes qui concernent les citoyens afin de les prendre en considération par les autorités compétentes, car elles représentent le deuxième œil des autorités publiques dans le pays. De ce qui précède, nous constatons l'importance des associations dans la vie du citoyen et de l'État, car elles sont un partenaire essentiel, surtout après la modification constitutionnelle de 2020. En conséquence, cette étude a été divisée en deux chapitres : le premier chapitre, intitulé "Le système juridique pour la création d'associations", et le deuxième chapitre, intitulé "L'organisation et le fonctionnement des associations". Puisque le droit de créer des associations est garanti constitutionnellement et est une demande sociale, la plupart des constitutions successives ont consacré ce droit, la plus récente d'entre elles étant la Modification constitutionnelle de 2020, qui stipule, à travers l'article 53, que le droit de créer des associations est garanti, et peut être exercé dès qu'il est déclaré, et réglementé par une loi organique.